Public finance management in Ukraine: problems and solutions - PETLENKO, Yuliia; KOTOVSKYI, Tymur (Scientific journal «World of Finance», 2019)
Introduction. Building an effective and fair system of public finance is an important stimulus for the dynamic development of economy of Ukraine. In this case, balance and rationality of financial resources of Ukraine will contribute to creating an enabling macroeconomic environment for business and investment growth and provide guaranteed stability in the system of social protection. However, imbalances and problems in public finances are able to form a threat to national economic development. According to this the article is devoted to coverage of topical issues of public financial management in Ukraine and defining their solutions via the implementation of a new model of government – the transfer of key business practices in public administration. Results. Main solution for issues in a public finance management should be the implementation of the new government model which is based on using main principles of corporate finance management in public area. New government model includes elastic system of compensation to public officers which is based on KPIs, decentralization of budget system and controlling by independent auditor. Conclusion. The implementation of a new model of public administration requires systematic and deep reforms, which required considerable significant time and financial resources.